Analisis Pemodelan Sistem Hibrid Proton Conducting Solid Oxide Fuel Cell (pSOFC) – Turbin Gas Mikro Pada Matlab-Simulink - Pranoto, Bayu; Tseng, Chung-Jen; Wardana, ING (Rekayasa Mesin, 2016)
This study simulated Proton Conducting Solid Oxide Fuel Cell (pSOFC) – Micro Gas Turbine (MGT) hybrid system on three different configuration. The first configuration use bypass hot gas from combustor going to fuel heater without  pass the turbine first. The second configuration use bypass hot gas out of turbine going to fuel heater. The third configuration is combined bypass out of combustor and also bypass out of turbine. The performance of these system are analyzed by using variation of operating pressure, fuel utilization (Uf), steam to carbon ratio (S/C), and bypass valve. Moreover, the impact of different bypass position were also evaluated. The result shows that the efficiency of using a double bypass hot gas flow after combustor and turbine is about 67%. This configuration became the best one among of another two configuration which proposed in this research.  The utilization of heat by using a double bypass hot flow gas after turbine and combustor has proven more effective to increase the system efficiency. Means that it can reduce the heat losses of the system.